Mesozoic sea dragons : Triassic marine life from the ancient tropical lagoon of Monte San Giorgio - Rieppel, Olivier (Life of the past., 2019)
Mesozoic Sea Dragons is a fascinating, in-depth look at marine life from the Middle Triassic Period, drawing upon the best marine fossil record for that period in the world.